Reduction in the thermodynamic nucleation barrier via the heteroepitaxial recrystallization mechanism. (15th July 2017) - Miller, V.M.; Payton, E.J.; Pilchak, A.L.
Abstract: A new recrystallization mechanism characterized by the formation of a coherent γ shell around a primary γ′ particle has been reported in superalloys [Charpagne et al. J. Alloy Compd. 688 (Part B) (2016) 685–694]. In the present work, the thermodynamics of nucleation by this mechanism are investigated, considering the stored deformation energy, interfacial energy, and elastic misfit. It is demonstrated that under realistic conditions, growth of any nucleus formed on a primary γ′ particle is thermodynamically favorable regardless of size. Graphical Abstract: